Single cell transcriptomes and multiscale networks from persons with and without Alzheimer’s disease - Wang, Qi; Antone, Jerry; Alsop, Eric; Reiman, Rebecca; Funk, Cory; Bendl, Jaroslav; Dudley, Joel T.; Liang, Winnie S.; Karr, Timothy L.; Roussos, Panos; Bennett, David A.; De Jager, Philip L.; et al. (Nature communications, 2024)
The emergence of single nucleus RNA sequencing (snRNA-seq) offers to revolutionize the study of Alzheimer’s disease (AD). Integration with complementary multiomics data such as genetics, proteomics and clinical data provides powerful opportunities to link cell subpopulations and molecular networks with a broader disease-relevant context. We report snRNA-seq profiles from superior frontal gyrus samples from 101 well characterized subjects from the Banner Brain and Body Donation Program in combination with whole genome sequences. We report findings that link common AD risk variants with CR1 expression in oligodendrocytes as well as alterations in hematological parameters. We observed an AD-associated CD83(+) microglial subtype with unique molecular networks and which is associated with immunoglobulin IgG4 production in the transverse colon. Our major observations were replicated in two additional, independent snRNA-seq data sets. These findings illustrate the power of multi-tissue molecular profiling to contextualize snRNA-seq brain transcriptomics and reveal disease biology. Multi-omic profiling of matched brain and peripheral tissues offer rare opportunities to uncover extra-CNS drivers of Alzheimer’s pathobiology. Here, authors report an Alzheimer’s linked CD83(+) microglia subtype that is associated with immunoglobulin IgG4 production in the transverse colon.